Leveraging video projects to promote active learning in a HyFlex speaking classroom - Sofyan, Ryan Rayhana; Aeni, Nur (Diksi, 2024)
This study explores the integration of student-created video projects within a HyFlex learning environment to enhance active learning and English speaking skills among students in Universitas Negeri Makassar. Utilizing a qualitative descriptive method, the research involved second-semester English Education Study Program students who enlisted in Interactive Speaking Course and participated in video-project assignments. Data were collected through interviews, classroom observations, and analysis of student-created videos. The findings provide insights into the impact of video projects on English speaking proficiency, particularly in terms of engagement and skill development. The result also identifies issues encountered related to technical features and resource availability. The study concludes by addressing the potential of video projects to support active learning and improve speaking proficiency in a HyFlex learning design.